Perancangan Aplikasi Presensi Peserta Seminar Di Perusahaan Cv. Sukses Berkah Berlimpah Dengan Metode Waterfall Menggunakan Qrcode - Muh. Fikri; Sofyan Mufti Prasetiyo (CV. Multi Kreasi Media, 2022)
Attendance has become an obligation when an event occurs. Attendance is a form of sign of the presence of participants in an event. Attendance fraud during seminar activities caused injustice among participants, so that many participants objected to the absence of participants and were then given the same seminar certificate by the organizers. Certificate is evidence obtained by seminar participants. Along with the development of technology, E-certificates emerged, namely certificates in digital form without the need to print them. With the support of the digital era and Industry 4.0, businesses need to keep up with the times. Today, almost every industry has a system, as well as a system for seminar attendance. This study describes the attendance information system and digital certificate creation. The system development method used in this research is the waterfall. Taking this method is to produce applications that suit user needs. With QR Code technology, it will facilitate the attendance process automatically and computerized and will minimize participant cheating in the attendance process, because the QR Code will change every meeting. The resulting system has a QR Code scanning feature from existing applications and will be recorded in the database on the server.